Boundary migration during recrystallization: experimental observations. Issue 1 (July 2015) - Zhang, Y B; Jensen, D Juul
Abstract: Quantitative analysis of boundary migration during recrystallization is a key task to understand the recrystallization process and to improve recrystallization models. In the last 25-30 years, quantification of boundary migration has mostly been conducted in term of average growth rates in many materials. This type of analysis has largely been based on the assumption that all or groups of recrystallizing grains grow in the same uniform manner, therefore the results represent average growth behaviors on a macro scale. Recently, significant efforts have been made to quantify the boundary migration during recrystallization on local grain scales, using different advanced experimental characterization and computer simulation techniques. This paper aims at summarizing these recent achievements with focus on the potentials of the various advanced experimental characterization techniques. Suggestions for new experimental and simulation work important for advancing the current understanding of local boundary migration are finally discussed.